Coronavirus vaccines will save 2021? “Light at the end of the tunnel” - Ricardo Santos de Oliveira (Brazilian Society for Pediatric Neurosurgery, 2021)
On 11 March, the WHO confirmed coronavirus disease 2019 as a pandemic. The Director-General of the WHO called on governments to change its course by taking "urgent and aggressive action" (1). In terms of the number of deaths COVID-19 has caused 1.919.126 deaths, reported to WHO as of January 10, 2021. (https://covid19.who.int).